Indicator displacement assay for cholesterol electrochemical sensing using a calix[6]arene functionalized graphene-modified electrode. Issue 1 (2nd December 2015) - Yang, Long; Zhao, Hui; Li, Yucong; Ran, Xin; Deng, Guogang; Zhang, Yanqiong; Ye, Hanzhang; Zhao, Genfu; Li, Can-Peng
Abstract : Indicator displacement assay for cholesterol (Cho) sensing using CX6–Gra against MB. Abstract : A novel electrochemical method has been developed towards cholesterol detection based on competitive host–guest interaction by selecting methylene blue (MB) and calix[6]arene functionalized graphene (CX6–Gra) as the "reporter pair". In the presence of cholesterol, the MB molecules are displaced by cholesterol in the CX6–Gra.MB complex, leading to a "switch off" electrochemical response. A linear response range of 0.50 to 50.00 μM for cholesterol with a low detection limit of 0.20 μM (S/N = 3) was obtained by using the proposed method. This method could be successfully utilized to detect cholesterol in serum samples, and may be expanded to the analysis of other non-electroactive species. Besides, the host–guest interaction between cholesterol and CX6 was studied by molecular modeling calculations, which revealed that the complexation could reduce the energy of the system and the complex of a 1 : 1 host–guest stoichiometry had the lowest binding free energy of −8.01 kcal mol −1 . In addition, the constructed electrochemical sensing platform is important as it does not use any enzyme or antibody for the detection of cholesterol efficiently and selectively over common interfering species.